PENGARUH PENAMBAHAN TINGKAT TEPUNG GAPLEK PADA PEMBUATAN SILASE LIMBAH SAYURAN TERHADAP KUALITAS FISIK DAN SIFAT KIMIAWI SILASE - Decka Wira Bangsa; Yusuf Widodo; Erwanto . (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The purpose of this research was to determine the effect and the best silage from the addition of different levels of cassava flour in the production of vegetable waste silage for texture, color, aroma, pH, Content of NH3, and value of silage fleigh. This research used a completely randomized design (CRD) with five treatments and three replications. The treatment in this research, namely vegetable waste without supplementation R0, R1 addition of 5% cassava flour, R2 addition of 10%cassava flour, R3 addition of 15% cassava flour, and R4 addition of 20% cassava flour.  The result showed that the additioning of different levels of cassava flour was significant (P <0.05) on  texture and value fleigh but not significant (P> 0.05) to color, aroma, pH, and content of NH. Treatment without supplementation (R0) was the best treatment that affects the texture of silage and the addition of 20% cassava flour (R4) of air-dried material was the best treatment that affect the value of fleigh silage. (Keywords: Silage, Cassava flour, Physical and Chemical characteristic).